Spin-orbit torque induced multi-state magnetization switching in Co/Pt Hall cross structures at elevated temperatures - Lim, Gerard Joseph (2020)
We demonstrate spin-orbit torque (SOT) driven multi-state magnetization switching in Co/Pt Hall crosses in the presence of varying externally applied in-plane fields from room temperature (RT = 295 K) to 360 K. In-situ Kerr imaging at various resistance states reveal the evolution of up and down magnetic domain expansion due to current-induced SOT switching. The control of magnetization states in the Hall cross is shown to be attributed to the non-uniform current-density and the resultant effective out-of-plane field due to the device geometry. The critical switching current density scales inversely with device temperature, and the SOT-driven change in Hall resistance varies across device temperatures and the applied in-plane fields. Additionally, the current-induced SOT efficiency, χsat, and the Dzyaloshinskii-Moriya interaction effective field, HDMI, at RT and 360 K are determined using the chiral domain wall model and current-induced loop-shift method. The χsat and HDMI values are found to decrease by ~15% and ~26%, respectively, with increasing device temperature. These results demonstrate the thermal sensitivity of current-induced SOT magnetization switching in multi-state devices.